PERAN PEMBERDAYAAN MASYARAKAT DAN TENAGA KESEHATAN DALAM MENANGGULANGI MALNUTRISI DI DESA AIR ANYIR KECAMATAN MERAWANG KABUPATEN BANGKA PROVINSI KEPULAUAN BANGKA BELITUNG - Syamsinar; Mubasysyir Hasanbasri (Journal of Health Service Management, 2022)
Background: Malnutrition is one of the causes of death in children under five years of age and has become one of the most threatening factors for children’s lives and health. Based on the nutritional status of weight and height index in the 2019 Bangka Belitung Islands Province Health Office data in Bangka, there were 0.84% wasting toddlers from 8,980 toddlers measured. In 2020, toddlerswith malnutrition were 0.63% of the 28,062 toddlers that were measured. Data recorded in February 2021 showed that from the 27,501 children under five who were measured and weighed, 1.13% of children were underweight and 0.64% with malnutrition. The Community Health Center (Puskesmas) has run nutrition improvement programs, including providing additional food, promoting healthand health services, nutrition counseling, and being active in the Kampung KB (Family Planning) program.Objectives: To find actors from both the Provincial/District/Village/Health Care Centre (Puskesmas) Governments/Communities who care to resolve malnutrition issues; to find daily activities in society that are obstacles to a healthy living culture; examine the role of community empowerment and health workers as well as the impact of empowerment toward the nutritional status of toddlers (children under five years old) in Air Anyir Village. Methods: A case study with an embedded single case design. Data were collected by in-depth interviews with twelve informants in February 2022 and then analysed by thematic analysis. Results: The informants of this research were 12 informants, namely family planning instructors, health workers as nutrition officers at Baturusa Health Center and Village Midwives, data managers for the nutrition program of the Health Service, community leaders as head of the Kampung KB, village officials fromthe village government, community leaders acting as TP PKK also serves as the head of the RT, community members who work as Posyandu cadres and parents of toddlers who visit the Posyandu. In Kampung KB, there is integrationand convergence in the implementation of empowerment and strengthening of family institutions to improve the quality of human resources, families, and communities. This study proves that the role of community empowerment andhealth workers in Kampung KB affected the nutritional status of the people in Air Anyir Village. The evidence (nutrition data of Baturusa Health Center) showed a decrease in cases of undernourished toddlers in Air Anyir Village.Conclusion: Actors in community empowerment include health cadres, TP PKK, village government, family planning extension workers, and health workers. Through the Kampung KB, the empowerment program in Air Anyir Village is going well. There is a decrease in cases of undernourished children underfive, although there are still bad habits in the community to hinder healthy living culture.